تعلق الحقوق والواجبات بالذمة ،وتجزء الأهلية تكامل أم انفصام؟ بين فقهاء الشريعة وفقهاء القانون - لشهب, أبو بكر (جامعة الوادي-university of eloued, 2015)
الذمة وعاء للأهلية عند البعض، ويرى آخرون أن المصطلحين لهما مفهوم واحد، واختلاف وجهات النظر بين شرّاح القانون، وفقهاء الشريعة، حول مفهوم الذمة ، حيث يرى الأولون تعدد الذمة المالية، وانتقالها ، خلافا لفقهاء الشريعة، ولم تتحد كلمتهم حول العلاقة بين الإثنين، كل ذلك يجعل للموضوع أهمية . وهذا البحث نتناول فيه المراد بكل واحد من الثلاث –( الذمة والأهلية والولاية )-، والعلاقة بينهم، ونقارن بين الموجود والثابت في الفقهين ( فقهاء الشريعة، وفقهاء القانون) نحدد نقاط الالتقاء ونقاط الافتراق، ونقف على النتائج المفيدة عند الاجتهاد. There has not been a common point of view regarding the meaning of protection and guardianship. Some use the terms interchangeably; while other consider protection as encompassing the term guardianship. Additionally, legal jurists and Shari'a scholars differed on their conception of 'protection' in that the former to consider the financial disclosure as multiple and transferable. What makes this issue worth studying is that the two types of jurists still differ on the relationship between the two concept. This study looks into the meaning of each of the three concepts (Protection, Eligibility and Mandate) and sheds light on the relationship amongst them. We also compare between the existent and the constant in the two types of jurisprudence (Shari'a and Law), defining the meeting points as well as the differences. The study concludes with the efficient outcomes resulting from due diligence (Ijtihad)
مقال
Keywords: الذمة - الأهلية - الولاية - الحماية; Edema – Eligibility – Mandate – Protection